Unintended Formation of a 26-Membered Cycle in the Course of a Novel Approach to Myricanol, a Strained [7,0]-Metacyclophane - Massé, Paul; Choppin, Sabine; Chiummiento, Lucia; Hanquet, Gilles; Colobert, Françoise (Synlett, 2020)
A convergent approach for the synthesis of (±)-myricanol, a strained diarylheptanoid isolated from Myricacae, was undertaken using a Suzuki–Miyaura coupling followed by a ring-closing metathesis (RCM). Herein, we report the unintentional formation of a 26-membered macrocycle as RCM product resulting from a head-to-tail dimerization of the seco-precursor, even in relay ring-closing metathesis (RRCM) conditions.
Keywords: myricanol; target-oriented synthesis; diarylheptanoid; natural product; macrocycle; Suzuki–Miyaura cross-coupling; RCM; Alzheimer’s disease; biological activities